Numerical analysis of slotted aerospike for drag reduction. (August 2019) - Manigandan, S.; Sruthisree, K N; Aich, Kaushali; Gunasekar, P.; Nithya, S.; Devipriya, J.; Venkatesh, S.
Abstract: One of the important criteria for designing high speed vehicles is drag reduction and aerodynamic heating. There are plenty of methods available however finding an economical and simple method for drag and heat flux reduction is very challenging. In this paper, the forward facing aerospike for blunt-nosed bodies is introduced at supersonic and hypersonic Mach numbers and tested for drag reduction. Initially, the flow fields are studied around the blunt cone with and without aerospike. In addition, the different shapes and L/D ratios flying at supersonic Mach 2 are computed numerically. The computational simulations is carried out to solve the three-dimensional steady Reynolds-averaged Navier-Stokes equation along with the k-ω turbulence model in computation solver. After comparing the flow properties around the various aerospike models, we have found that the flat aerodisk experiences a drastic pressure reduction on the blunt nose cone but it has relatively less heat flux reduction. Consequently, a slotted aerodisk modification design has been analysed which uses convection flow to reduce heat flux.